NEW DATA ON THE STRUCTURE AND TEXTURE OF BAER HUMMOCKS - Svitoch A.A.; Klyuvitkina T.S. (My University, 2004)
The North Caspian region between the Kuma River mouth and the Emba River hosts several submeridional ridges and mounds (Baer hummocks), which are named after K. Baer who described them. Despite the long history of study and the numerous hypotheses that have been proposed, the origin of these structures remains largely enigmatic, because their structure (stratification and textures) have been insufficiently studied to date. Factual data on their sediments are limited and have been insufficiently analyzed. However, only the study of the internal structure of the hummocks can substantially clarify their origin or, at least, promote the prospecting for such structures. Lithostructural features of the hummock sequences suggest that they are composed of not only eolian (or marine sediments, but also a significant share of shallow-marine, subaerial deltaic, and subaqueous deltaic sediments. Hummocks are clearly confined to the paleodeltas of the Khvalynian transgression area. The architecture of hummocks and the structural diversity of sediments therein contradict notions that their origin was a result of erosion or subaqueous slumping. Numerous measurements of the divergence between the dip angles of beds and strikes of the long axis of the hummocks also testify against sedimentation in the direction parallel to their long axes in eolian (or aqueous) settings.